UNDERSTANDING FAMILY LAW AS A SOLUTION TO PREVENT SEXUAL VIOLENCE AGAINST CHILDREN AND WOMEN - Irfan Islami (INTERNATIONAL JOURNAL OF SOCIETY REVIEWS, 2025)
Marriage is a legal event founded on a mutual commitment between a man and a woman to build a lasting and eternal household. However, as time passes and the life of a husband and wife progresses, problems often become part of the dynamics of domestic life. Domestic problems often result in sexual violence against children and women in particular. The role of the family in creating harmony and comfort has a significant impact on ensuring the safety of women, especially children and wives. Domestic violence, which is often experienced by women and children, is not solely the responsibility of the two individuals in the household. The role of the state is crucial in protecting and resolving issues of sexual violence in accordance with applicable law. This article aims to provide public understanding, particularly regarding family law and how to protect women and children to prevent sexual violence. A good understanding of family law is expected to be a preventative measure against sexual violence against women and children.